The Use of FDG PET Parametric Imaging in the Diagnosis of Olivopontocerebellar Atrophy. (September 2020) - Harfouch, Nassier; Finkelstein, Mark; Sathe, Swati; Raden, Mark; Brenner, Arnold I.
Abstract : Abstract: Olivopontocerebellar atrophy is a rare neurodegenerative syndrome associated with 2 distinct disorders: multiple system atrophy and spinocerebellar ataxia. We present a case involving a 66-year-old man with adult-onset progressing cerebellar signs reflective of a cerebellar syndrome with no significant family history and unremarkable genetic testing for spinocerebellar ataxia. This case was found to be most consistent with sporadic olivopontocerebellar atrophy, which falls under the multiple system atrophy category. This diagnosis can be made using 18 F-FDG PET/CT scanning and with MRI in some cases. However, in this case, relatively new PET/CT quantification and parametric imaging software was used for analysis, CortexID Suite.